Dual Right Coronary Artery Associated with ASD and Pulmonary Stenosis - Rahman, F; Subedi, Bikash; Anam, Khairul; Akhter, N; Banerjee, Sajal; Uddin, MS; Hossain, ATM Iqbal; Ahmed, CM; Haque, KMHS Sirajul (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Coronary artery anomalies occur in less than 1% of the cases undergoing coronary angiography, and constitute 1-2% of all congenital heart disease. The origin of the circumflex artery from the right coronary artery (RCA) or the right sinus of Valsalva is the most commonly encountered anomaly and is usually well tolerated 2. We report the clinical , echocardiographic and angiographic findings of symptomatic 45 years elderly lady with the atrial septal defect and double right coronary artery and pulmonary stenosis. To our knowledge, such associated lesion as founding this case has not been reported in the literature till date at home and abroad. DOI: 10.3329/jbcps.v28i2.5374 J Bangladesh Coll Phys Surg 2010; 28: 125-127